MONOPOLY OF STATE-OWNED ENTERPRISE OF SOCIAL JUSTICE - Akyuwen, Rory Jeff (Faculty of Law, Pattimura University, 2017)
The role of the state through BUMN becomes so important when it is formulated in a provision as formulated in Article 33 Paragraph (2) of the 1945 Constitution of the State of the Republic of Indonesia, where the production branches which are important for the State and which affect the livelihood of the public must be controlled by Country. Here it indicates the authority of the State to participate in economic activities through the operation of production branches that can be categorized as important for the State and considered vital and strategic for the interest of the State.This is based on the reasons as formulated in the explanatory section of Article 33 of the 1945 Constitution of the State of the Republic of Indonesia, so that the benefits of the production branches do not fall into the hands of individuals, the State actively takes the role to cultivate it because the production branch is considered important and which control the livelihood of the people for the greatest prosperity of the people. State-Owned Enterprises is formed with the aim of contributing to the development of the national economy in general and the state's revenue in particular; The pursuit of profit; To hold general benefit in the form of providing goods and / or services of high quality and adequate for the fulfillment of the livelihood of the public; Pioneering business activities that have not yet been implemented by the private sector and cooperatives and actively providing guidance and assistance to weak economic entrepreneurs, cooperatives, and communities.SOEs are given the right to monopoly in the economic field which is considered to control the livelihood of many people.